PENGARUH PIJAT OKETANI DAN KOMPRES DAUN KUBIS TERHADAP KEJADIAN BENDUNGAN ASI PADA IBU MENYUSUI DI CIPUTAT - H, Tya Wahyu; Sari, Agustina; Nency, Aprilya (SINERGI : Jurnal Riset Ilmiah, 2025)
Breast engorgement or breast swelling in breastfeeding mothers is caused by increased milk production exceeding storage capacity. Non-pharmacological treatment for breast engorgement includes Oketani massage and cold cabbage leaf compresses. This study aims to determine the effect of Oketani massage and cold cabbage leaf compresses on the incidence of breast engorgement based on the SPES Scale in Ciputat in 2025. The population and sample of this study were 2 breastfeeding mothers (primi) who experienced breast engorgement and then underwent Oketani massage and cold cabbage leaf compresses for 3 consecutive days. This study was conducted with an experimental approach and was conducted directly with breastfeeding mom who experienced breast engorgement. Qualitative research using a case study method was conducted directly with breastfeeding mothers who experienced breast engorgement. The results of the study on the first patient who received the Oketani massage intervention showed a decrease in breast engorgement intensity from a 5 (moderate) to a 1 (mild) scale. The second patient who received the cold cabbage leaf compress intervention saw a decrease in breast engorgement or breast engorgement intensity from a 5 (moderate) to a 3 (mild) scale. In conclusion, the Oketani massage intervention was more effective in reducing breast engorgement or breast engorgement in breastfeeding mothers compared to the cold cabbage leaf compress intervention.